Risk Mitigation of Tobacco Supply Chain: Business Process Model - Silvana Maulidah (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2020)
Tobacco and its industrial products are a massive business in international trade. As a potential agro-industry, the tobacco products industry requires a supply of raw materials that must meet quantity, quality and continuity. The complexity of the tobacco supply chain network and the rapidly changing world business dynamics, pose risks in its business processes. An optimal supply chain risk mitigation or risk management strategy needs for the resilience of the tobacco supply chain in the disruption. The purpose of this study is to analyze the level of risk priority and also to formulate a risk mitigation strategy for the tobacco supply chain through a business process model approach. The method of analysis is the Delphy method and the House of Risk (HoR). The business process adopted from the SCOR (Supply Chain Operations Reference) model. The results showed: the priority level of tobacco supply chain risk is: economic uncertainty, tobacco is not available at the farm level, the location of tobacco raw materials is far from production activities, product prices have risen due to customs and product demand has increased sharply. Supply chain risk of mitigation strategies includes: increasing the flow of information in the tobacco supply chain, managing the stock/supply of tobacco raw materials and processed products, evaluating distributor selection, establishing partnerships with tobacco farmers, implementing a marketing mix strategy (product, price, location, promotion), increasing coordination with relevant governments, and management of information systems and technology.